2019
DOI: 10.3390/cancers11040569
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Platelets in Cancer Pathophysiology: Focus on Malignant Glioma

Abstract: The link between thrombocytosis and malignancy has been well known for many years and its associations with worse outcomes have been reported mainly for solid tumors. Besides measuring platelet count, it has become popular to assess platelet function in the context of malignant diseases during the last decade. Malignant gliomas differ tremendously from malignancies outside the central nervous system because they virtually never form distant metastases. This review summarizes the current understanding of the pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 87 publications
0
23
0
1
Order By: Relevance
“…IPA analysis of BMT spheres showed up-regulation of PD1/PDL1 pathway and inhibition of calciuminduced T lymphocyte apoptosis. PD-L1 is not constitutively expressed in tumor cells but rather is inducibly expressed (i.e., adaptive immune resistance) in response to in ammatory signals (77,78).…”
Section: Discussionmentioning
confidence: 99%
“…IPA analysis of BMT spheres showed up-regulation of PD1/PDL1 pathway and inhibition of calciuminduced T lymphocyte apoptosis. PD-L1 is not constitutively expressed in tumor cells but rather is inducibly expressed (i.e., adaptive immune resistance) in response to in ammatory signals (77,78).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, platelet activation has been implicated in GBM tumor growth 44 . Previous studies have found that levels of sphingosine-1-phosphate (S1P), a lipid signaling molecule secreted by platelets that has been implicated as a modulator of inflammation and tumorigenesis, is significantly elevated in GBM tumors 45 . S1P drives the transformation of macrophages into tumor associated macrophages (TAMs), which play a role in driving tumor cell invasion by suppressing the immune system in the tumor microenvironment 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Platelets are small anucleate cell fragments circulating in the blood, originally derived from megakaryocytes in the bone marrow. While the relevance of platelet activation for blood clot formation after vascular injury is well established, more exploratory research has shown that platelets contribute to the (patho)physiological processes important for cancer, inflammation, infection, and neurological diseases . The parallel between platelets and serotonergic neurons was drawn in the early 1970s .…”
Section: Parallels Between Platelets and Neuronsmentioning
confidence: 99%
“…While the relevance of platelet activation for blood clot formation after vascular injury is well established, more exploratory research has shown that platelets contribute to the (patho)physiological processes important for cancer, inflammation, infection, and neurological diseases. [13][14][15][16] The parallel between platelets and serotonergic neurons was drawn in the early 1970s. 17,18 The link with neurological disorders still mostly relates to the similarities between the platelet release reaction of stored agonists following stimulation and the neurotransmitter release following an action potential in a neuron ( Figure 1).…”
Section: Parallels Between Platelets and Neuronsmentioning
confidence: 99%